2019
DOI: 10.1101/716837
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rapid degradation ofC. elegansproteins at single-cell resolution with a synthetic auxin

Abstract: As developmental biologists in the age of genome editing, we now have access to an ever-increasing array of tools to manipulate endogenous gene expression. The auxin-inducible degradation system, allows for spatial and temporal control of protein degradation, functioning through the activity of a hormone-inducible Arabidopsis F-box protein, transport inhibitor response 1 (TIR1). In the presence of auxin, TIR1 serves as a substrate recognition component of the E3 ubiquitin ligase complex SKP1-CUL1-F-box (SCF), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…In these same cells it was observed that after removal from an auxin treatment GFP signal would begin to recover [10]. Since Nishimura's experiment, the system has successfully been used in fission yeast, Drosophila melanogaster, Caenorhabditis elegans, zebrafish, and mouse oocytes [2,3,4,11,12].…”
Section: The Auxin-inducible Degron (Aid) Systemmentioning
confidence: 99%
See 4 more Smart Citations
“…In these same cells it was observed that after removal from an auxin treatment GFP signal would begin to recover [10]. Since Nishimura's experiment, the system has successfully been used in fission yeast, Drosophila melanogaster, Caenorhabditis elegans, zebrafish, and mouse oocytes [2,3,4,11,12].…”
Section: The Auxin-inducible Degron (Aid) Systemmentioning
confidence: 99%
“…1). The SCF complex is highly conserved among eukaryotes, which allows the transplant of specific Fbox proteins from one organism to another to form a functional SCF complex that can direct the degradation of proteins tagged with the target degron [1,3,4]. In the C. elegans AID system, the exogenous F-box protein used is the Arabidopsis thaliana transport inhibitor response 1 (TIR1) protein [2].…”
Section: The Auxin-inducible Degron (Aid) Systemmentioning
confidence: 99%
See 3 more Smart Citations